Effectiveness of digital technology interventions to reduce loneliness in adults: a protocol for a systematic review and meta-analysis - Syed Ghulam Sarwar Shah; David Nogueras; Hugo van Woerden; Vasiliki Kiparoglou (BMJ Open)
Introduction Loneliness is an emerging public health problem that is associated with social, emotional, mental and physical health issues. The application of digital technology (DT) interventions to reduce loneliness has significantly increased in the recent years. The effectiveness of DT interventions needs to be assessed systematically.Methods and analysis Aim: To undertake a systematic review and meta-analysis on the effectiveness of DT interventions to reduce loneliness among adults.Design: Systematic review and meta-analysis.Data sources: PubMed, Medline, CINAHL, EMBASE and Web of Science.Publication period: 1 January 2010 to 31 July 2019.Inclusion criteria: Primary studies involving the application of DT interventions to reduce loneliness, involving adult participants (aged ≥18 years), follow-up period ≥3 months and published in the English language.Synthesis and meta-analysis: A narrative summary of the characteristics of included studies, findings by the type of DT intervention, and the age, gender and ethnicity of participants. A meta-analysis by the study design and duration of follow-up and determination of random effects size using the RevMan V.5 software.Quality of evidence and bias: Quality of evidence assessed the RoB V.2.0 (revised tool for Risk of Bias in randomized trials) and ROBINS-I (Risk Of Bias in Non-randomized Studies—of Interventions) tools for randomised control trials and non-randomised studies, respectively. Heterogeneity between studies will be determined by the I2 and Cochran’s Q statistics and publication bias checked with funnel plots and the Egger’s test.Ethics and dissemination Ethics approval was not required for this protocol. The findings will be disseminated through journal articles and conference presentations.PROSPERO registration number CRD42019131524